SISTEM PENDUKUNG KEPUTUSAN PENENTUAN GURU BERPRESTASI MENGGUNAKAN METODE TOPSIS (STUDI KASUS: DINAS PPO KAB. TTU) - Jeri Aurelianus Sede; Yoseph P.K Kelen; Darsono Nababan (Department of Information Technology, Universitas Timor, Indonesia, 2023)
This study aims to assist human work in knowing the decision support system for determining outstanding teachers using the topsis method using the Multi Attribute Decision Making (MADM) decision making method which is used to evaluate or select several alternatives as a decision support system using one method, namely the The trick for order preference by similarity to ideal solution (TOPSIS). This method is widely used to solve practical decision-making. This is because the concept is simple and easy to understand, computation is efficient, and has the ability to measure the relative performance of decision alternatives. There are 5 criteria used in determining outstanding teachers, namely pedagogic, personality, professional, social and innovation. From the results of calculations using the cicue for order preference by similarity to ideal solution (TOPSIS) method, the teacher who was selected as an outstanding teacher was Elisabeth Abi S.PD SD with a score of 0.825. Thecnicue for order preference by similarity to ideal solution (TOPSIS) method makes it easy to determine outstanding teachers at the youth and sports education office at TTU, this is web-based and uses the PHP programming language.